(untitled) (Journal of actual problems of jurisprudence, 2019)
At present, investment legislation of the Republic of Kazakhstan is quite developed, but some difficulties in providing the legal interests of investors still exist. In particular, today, in the first place there is the problem of creating the right conditions for investment activities in a worsening of the legal status of the investor in connection with a radical modernization of the investment legislation. In such circumstances it is necessary to further improve the rules of special legislation in order to bring them into line with the current international legal practice management investment relations. Keywords: legislation, investment activity, investment relations.